PDM-Coulombic effects of non-inertial cosmic strings on a Klein-Gordon oscillator - Boumali, A.; Bouzenada, A.; Messai, N.; Mustafa, O. (Soc Mexicana Fisica, 2024)
This paper addresses the problem of a three-dimensional Klein-Gordon oscillator with position-dependent mass in a non-inertial cosmic string background. We provide solutions to this problem and analyze the eigensolutions, considering the influence of non-inertial effects and the presence of position-dependent mass (PDM) on the eigenvalues. Expressions are obtained for the bound state energies and wave functions.
Keywords: Non-inertial cosmic string; Klein-Gordon oscillator.